A new species of Allophryne (Anura: Allophrynidae) from the Atlantic rain forest biome of eastern Brazil - Caramaschi, Ulisses (2013)
A new species of the genus Allophryne is described and, in contrast to its congeners that occurin the Amazon Basin, is based on specimens obtained in Uru¸cuca, State of Bahia, in the Atlantic Rain Forest of eastern Brazil. Allophryne relicta sp. nov. is characterized by a medium body size for the genus (snout-vent length range 19.9-21.9 mm in males); large head (head width about 35% of SVL); large, red-orange eyes, with a large black transversal stripe on iris; dorsum covered by few tubercles and many scattered black dots; dorsolateral surfaces cream with dark brown, elongate, anastomosed spots, and venter clear gray with scattered small white tubercles; presence of a line of tubercles on the ventrolateral surface of forearm; advertisement call formed by a multi-pulsed note of 0.509 6 0.029 s in duration and emitted at intervals of 1.287 6 0.500 s, with notes composed of 28.58 6 1.84 pulses at a dominant frequency of 3828 6 82.28 Hz; call-note emission rate of 34.46 notes/min and pulse emission rate of 56.13 6 1.25 s. The molecular phylogeny supports the placement of A. relicta sp. nov. as sister taxon of a clade formed by A. resplendens + A. ruthveni.